Specification for installation of gas fires, convector heaters, fire/back boilers and decorative fuel effect gas appliances. Inset live fuel effect gas fires of heat input not exceeding 15 kW, and fire/back boilers (2nd and 3rd family gases) Part 2, (15th April 2001) - British Standards Institution,
No abstract available